2019
DOI: 10.1192/bjp.2019.74
|View full text |Cite
|
Sign up to set email alerts
|

The association of late-life depression with all-cause and cardiovascular mortality among community-dwelling older adults: systematic review and meta-analysis

Abstract: BackgroundLate-life depression has become an important public health problem. Available evidence suggests that late-life depression is associated with all-cause and cardiovascular mortality among older adults living in the community, although the associations have not been comprehensively reviewed and quantified.AimTo estimate the pooled association of late-life depression with all-cause and cardiovascular mortality among community-dwelling older adults.MethodWe conducted a systematic review and meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(77 citation statements)
references
References 37 publications
(35 reference statements)
2
62
0
4
Order By: Relevance
“…Specifically, it has been reported that social distancing measures, have been associated with depression and loneliness, especially among older adults [14][15][16]. It is known that depression and anxiety have strong adverse effects on blood pressure levels, glycemic control, compliance to medications, as well as to CVD risk [17,18]. Furthermore, social distancing measures may promote sedentary behavior and adoption of unhealthy dietary habits, especially for people living alone [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been reported that social distancing measures, have been associated with depression and loneliness, especially among older adults [14][15][16]. It is known that depression and anxiety have strong adverse effects on blood pressure levels, glycemic control, compliance to medications, as well as to CVD risk [17,18]. Furthermore, social distancing measures may promote sedentary behavior and adoption of unhealthy dietary habits, especially for people living alone [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Some of the deaths due to the measures taken happen acutely (eg, due to people with acute myocardial infarction not coming to the hospital for care), 7,8 but the majority may accrue over longer periods of time (Table 1). There is strong evidence on the adverse effects of unemployment, financial crises, depression, and social isolation on long-term morbidity and mortality, [9][10][11][12][13][14] but caution is needed to extrapolate this evidence to the current situation which is unprecedented in terms of the acuteness and massive impact of the measures taken. Some projections have been made for these excess deaths, and evidence is already accumulating for some of these excess death causes.…”
Section: Covid-19 Versus From Measures Takenmentioning
confidence: 99%
“…A recent systematic literature review and meta-analysis, which included 49 cohort studies, found that late-life depression increased the risk of all-cause mortality by 34%. 14 The figure was mainly derived from studies undertaken in HICs. In comparison, our study showed a stronger impact of depression on all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%